An adsorbent and a method for preparing the same
Patent Information
- Application Number
- CN202510531236.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-25
- Publication Date
- 2026-10-27
AI Technical Summary
但是,该技术采用喷雾干燥法直接成型造粒,不利于改烧物料混合的均匀性
[0036](1)本发明提供的吸附剂的制备方法,首先在混合打浆步骤形成了组成均匀的混合浆液,混合浆液中较高的粘土添加比例为后续转动成型步骤提供了牢固粘结的粉末物料;在喷雾造粒过程中,分子筛原粉和粘土成分中的氧化硅和氧化铝因为高温脱水使得彼此之间结合牢固;在转动成型过程中,由于微球颗粒具有一定的粒度分布,使得转动成型时微球粒子之间的压紧程度较好。
Smart Images

Figure BDA0005378593640000091 
Figure BDA0005378593640000093 
Figure BDA0005378593640000101
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen energy, specifically relating to an adsorbent and its preparation method. Background Technology
[0002] The hydrogen energy industry chain includes hydrogen production, storage and transportation, refueling, and comprehensive applications of hydrogen (fuel cells). From the hydrogen production perspective, hydrogen production currently mainly involves several pathways, including industrial by-product hydrogen, fossil fuel-based hydrogen production, and renewable energy-based hydrogen production. Among these, industrial by-product hydrogen, after direct purification, can be supplied to hydrogen refueling stations via long-tube trailers to meet the hydrogen needs of fuel cells, making it one of the lowest-cost hydrogen sources on the market. Among various purification methods, pressure swing adsorption (PSA) technology produces high-purity hydrogen, capable of extracting hydrogen with a purity of 99%-99.999% from various hydrogen-containing gases, and controlling various impurities to trace levels. It is currently the most economical and feasible technology for purifying and producing hydrogen for fuel cells.
[0003] Adsorbents are undoubtedly one of the core components of hydrogen pressure swing adsorption (PSA) purification technology, and low-cost, high-performance, and stable adsorbent preparation technology has always been a goal pursued in this field. Current methods for preparing molecular sieve adsorbents for PSA purification mainly employ binder-free processes, which include three stages: molding, crystallization, and exchange. The molding stage often involves dry mixing of molecular sieve powder and clay powder, followed by the direct addition of water or a binder for rotary molding.
[0004] However, the hydrophilicity and hydrophobicity of molecular sieve powder and clay powder differ significantly. Clay is more hydrophilic, while the commonly used 5A molecular sieve is more hydrophobic, and the X molecular sieve is more hydrophobic than 5A. Since dry mixing is a mechanical mixing process, the difference in hydrophilicity and hydrophobicity between the molecular sieve powder and clay powder inevitably leads to uneven mixing. Furthermore, before mixing, the two powders are usually homogenized into 2-3 μm particles. However, the uniform particle size results in poor compaction between particles during rotational molding, making it difficult to form spheres. Even if spheres are formed, the mechanical strength of the resulting spheres is often poor.
[0005] Therefore, the conventional method of dry mixing followed by direct rotation molding cannot achieve the effect of uniform mixing and firm bonding of powder materials, resulting in a long molding time, unstable content of various components and adsorption performance of adsorbent spheres, and poor mechanical strength.
[0006] CN105536696A discloses an adsorbent for removing heavy metals and ammonia nitrogen from wastewater and its preparation method. The method involves adding additives and clay, thoroughly mixing them with catalyst filter residue, and then spray-drying to obtain microspheres with a particle size of 50-60 μm. These microspheres are then mixed evenly with water, additives, and clay, and shaped into adsorbents using methods such as extrusion, ball rolling, or tableting. However, this technique, which involves further mixing the spray-dried microspheres with clay and other powders, is not conducive to the uniformity of the mixed materials.
[0007] CN101007261A discloses a zeolite adsorbent and its preparation method. The method involves uniformly mixing zeolite, filler, clay, a pore-forming agent, and acid to prepare a slurry. The slurry is then spray-dried to obtain powdered particles with a particle size of 20-500 μm, which are the zeolite adsorbent. However, this technology uses spray drying for direct granulation, which is not conducive to the uniformity of the mixed materials.
[0008] Therefore, there is a need to provide a new adsorbent forming method to solve problems such as uneven material mixing, weak bonding, and unstable adsorption performance during the forming of molecular sieve adsorbents. Summary of the Invention
[0009] To address the aforementioned technical problems, the present invention aims to provide an adsorbent and its preparation method.
[0010] To achieve the above objectives, the present invention provides a method for preparing an adsorbent, wherein the preparation method includes:
[0011] Step 1: Mix the powder and water to form a slurry, then spray the slurry to obtain microspheres.
[0012] Step 2: The microspheres are rotated and shaped in the presence of a binder to obtain an adsorbent precursor, which is then dried and calcined to obtain the adsorbent.
[0013] Among the microspheres, the proportion of particles with a diameter distribution of 20-80 μm is ≥85 wt%, and the average particle size of the microspheres is 29-72 μm.
[0014] According to a specific embodiment of the present invention, preferably, the mixed powder comprises 40wt%-70wt% molecular sieve powder and 30wt%-60wt% clay on a dry basis. Since the main chemical components of both the molecular sieve powder and the clay are aluminosilicates, the present invention mixes the molecular sieve powder, clay, and water to form a uniform slurry during the mixing and pulping process. Simultaneously, the higher proportion of clay added provides a firmly bonded powder material for the subsequent rotational molding step.
[0015] In some specific implementations, the amount of water added during the mixing and pulping process can be adjusted as needed.
[0016] According to a specific embodiment of the present invention, preferably, the molecular sieve raw powder is type A molecular sieve raw powder and / or type X molecular sieve raw powder, such as 4A molecular sieve raw powder or 13X molecular sieve raw powder.
[0017] According to a specific embodiment of the present invention, preferably, the clay is kaolin and / or attapulgite.
[0018] According to a specific embodiment of the present invention, preferably, the binder comprises one or a combination of two or more of water, starch, and sodium carboxymethyl cellulose. When starch and sodium carboxymethyl cellulose are used, an aqueous solution of appropriate concentration can be prepared for use according to actual needs.
[0019] According to a specific embodiment of the present invention, preferably, the spray granulation process is as follows: the mixed slurry is fed into the spray drying tower using a peristaltic pump, and spray granulation is performed by an atomizing wheel.
[0020] According to a specific embodiment of the present invention, preferably, the temperature of the spray drying tower is 150-230°C.
[0021] According to a specific embodiment of the present invention, preferably, the pumping speed of the peristaltic pump is 40-50 rpm.
[0022] According to a specific embodiment of the present invention, preferably, the rotational speed of the atomizing wheel is 8000-15000 rpm.
[0023] In this invention, the particle size and fine powder content of microspheres can be controlled by adjusting process conditions such as the peristaltic pump speed and the atomizing wheel rotation speed.
[0024] According to a specific embodiment of the present invention, preferably, the rotational molding is carried out while the binder is being sprayed, with a rotational speed of 50-80 rpm. During the rotational molding process, the fine powder in the container is carried to the upper part of the container due to friction and centrifugal force, and then rolls down under the action of gravity. This rotational action is used to bind the fine powder together, causing the microspheres to grow into spherical particles.
[0025] In some specific implementations, the rotational molding process can also be carried out by intermittently spraying adhesive during rotation, with the spraying frequency and amount adjusted according to the growth of the small balls.
[0026] According to a specific embodiment of the present invention, preferably, during the rotational molding process, the total amount of the sprayed binder accounts for 38wt%-55wt% of the total dry basis of the mixed powder.
[0027] According to a specific embodiment of the present invention, preferably, the calcination temperature is 450-550℃ and the calcination time is 1-2 hours.
[0028] In this invention, the spheroidization process of the adsorbent mainly includes a nucleation stage and a spheroid growth stage. Regarding the nucleation stage, on one hand, the microspheres obtained through mixing, pulping, and spray granulation can directly serve as "seeds," becoming the core for the subsequent spheroid growth stage. At this point, the spray granulation process that generates the "seeds" can be considered the nucleation stage. On the other hand, when further rotating and shaping occurs, smaller powder particles or fine powders will come into contact with the sprayed liquid, causing the liquid to form discontinuous bridging around some of the powder particles' contact points, resulting in localized particle aggregation into loose aggregates, called nuclei. As the container rotates, the particles press against each other, reducing the voids. When the aggregates continue to come into contact with the sprayed liquid and other powder particles, they can further generate larger aggregates, which can also be called "seeds." This process of generating "seeds" can also be called the nucleation stage.
[0029] During the spherical growth stage, the uniform distribution of liquid between particles in the generated "seeds" gives them plasticity. The spray granulation process provides uniformly mixed powder for this stage. Under the influence of liquid surface tension and negative pressure, the powder adheres directly to the wetted surface of the rotating "seeds," causing them to grow into spherical particles. Simultaneously, the rotational motion and the compaction of the generated spherical particles cause the molded material to grow larger and more compact, eventually forming even larger spherical particles. This spherical growth stage is also the main process of rotational molding.
[0030] Therefore, the generation of "seeds" in the nucleation stage is the foundation of rotational granulation. During the sphere growth stage, the sphere formation can be controlled by adjusting parameters such as the amount of binder sprayed and the rotational speed during granulation. Furthermore, in both stages, the uniformity of the powder raw material mixing affects the composition of the "seeds" and spheres, while the particle size distribution of the powder raw material affects the ease of "seed" and sphere formation. Both the uniformity of the powder raw material mixing and the particle size distribution can be controlled through the spray granulation process parameters. The synergistic effect of these factors ultimately influences the elemental composition and adsorption performance stability of the adsorbent formed in the same batch, as well as the mechanical strength of the adsorbent.
[0031] The present invention also provides an adsorbent prepared by the above-described preparation method.
[0032] According to a specific embodiment of the present invention, preferably, the particle size of the adsorbent is 1.6-2.5 mm.
[0033] In some specific embodiments, preferably, the adsorbent comprises 5wt%-18wt% Na2O, 36wt%-45wt% Al2O3, and 42wt%-50wt% SiO2; the remainder being unavoidable impurities.
[0034] In this invention, the elemental composition of adsorbents prepared in the same batch exhibits good consistency and repeatability, as shown in the following ways: Under the same preparation conditions, the relative standard deviation of Na₂O content in the same batch of adsorbents is within 1%, the relative standard deviation of Al₂O₃ content is within 0.35%, and the relative standard deviation of SiO₂ content is within 0.4%. Under the same preparation conditions, the relative standard deviation of static water adsorption capacity in the same batch of adsorbents is within 2.5%. Under the same preparation conditions, the relative standard deviation of crushing resistance in the same batch of adsorbents is within 2%.
[0035] Unlike conventional molecular sieve adsorbent molding methods that involve mixing dry powders, gradually adding water, and slowly rotating to generate "seeds" and grow them into spheres, the advantages of this invention are:
[0036] (1) The method for preparing the adsorbent provided by the present invention firstly forms a uniformly composed mixed slurry in the mixing and pulping step. The high clay addition ratio in the mixed slurry provides a firmly bonded powder material for the subsequent rotational molding step. In the spray granulation process, the silica and alumina in the molecular sieve powder and clay components are firmly bonded to each other due to high-temperature dehydration. In the rotational molding process, the microspheres have a certain particle size distribution, resulting in good compaction between the microspheres during rotational molding.
[0037] (2) The adsorbent provided by the present invention has uniform elemental composition, stable adsorption performance and high mechanical strength in the same batch. Detailed Implementation
[0038] In order to provide a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention will now be described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.
[0039] Raw material source:
[0040] (1) 4A molecular sieve raw powder, specifications: static water adsorption capacity ≥26%, packaged product moisture content ≤21%; manufacturer: Luoyang Jianlong Micro-Nano New Materials Co., Ltd.
[0041] (2) 13X molecular sieve raw powder, specifications: static water adsorption capacity ≥32%, packaged product moisture content ≤23%; manufacturer: Luoyang Jianlong Micro-Nano New Materials Co., Ltd.
[0042] (3) Kaolin, Specification: Powdered S-II type, Moisture content ≤16%; Manufacturer: China Kaolin Co., Ltd.
[0043] Analysis and testing methods:
[0044] (1) The content of the main components in the adsorbent is determined by the standard for determination of elemental content (GB / T 30905-2014).
[0045] (2) The static water adsorption capacity of the adsorbent was determined by static N2 adsorption according to the standard of molecular sieve static water adsorption determination method (GB / T 6287-2021).
[0046] Example 1
[0047] This embodiment provides a method for preparing an adsorbent, the specific steps of which are as follows:
[0048] Step 1: Mix 500g of 4A molecular sieve raw powder (with a water content of 20%), 705g of kaolin (with a water content of 15%) and 1294g of water at room temperature for 1 hour to form a uniform slurry. Then, use a peristaltic pump to send the slurry into a spray drying tower and spray it through an atomizing wheel to obtain microspheres.
[0049] The average particle size of the microspheres is 55 μm, and the proportion of microspheres with a particle size distribution of 20-80 μm is 95 wt%.
[0050] The spray drying tower has an internal temperature of 180°C, a peristaltic pump speed of 50 rpm, and an atomizing wheel speed of 10,000 rpm.
[0051] Step 2: Place the above microspheres into a coating machine (model BY300A) for rotational molding at a speed of 80 rpm, while spraying a total of 380 grams of water until the microspheres grow into moist spheres of 1.6-2.5 mm, which is the adsorbent precursor; dry the adsorbent precursor at 120°C for 1 hour, and then calcine it at 500°C for 2 hours to obtain adsorbent A.
[0052] Four samples were randomly selected from adsorbent A and numbered A1, A2, A3 and A4 respectively. The test results of the component content, static water adsorption capacity and crush resistance of each sample are shown in Table 1 and Table 2.
[0053] Example 2
[0054] This embodiment provides a method for preparing an adsorbent, the specific steps of which are as follows:
[0055] Step 1: Mix 875g of 4A molecular sieve raw powder (with a water content of 20%), 353g of kaolin (with a water content of 15%) and 1272g of water at room temperature for 1 hour to form a uniform slurry. Then, use a peristaltic pump to send the slurry into a spray drying tower and spray it through an atomizing wheel to obtain microspheres.
[0056] The average particle size of the microspheres is 72 μm, and the proportion of microspheres with a particle size distribution of 20-80 μm is 93 wt%.
[0057] The spray drying tower has an internal temperature of 150°C, a peristaltic pump speed of 50 rpm, and an atomizing wheel speed of 8000 rpm.
[0058] Step 2: Place the above microspheres into a coating machine (model BY300A) for rotational molding at a speed of 60 rpm, while spraying a total of 475 grams of water until the microspheres grow into moist spheres of 1.6-2.5 mm, which is the adsorbent precursor; dry the adsorbent precursor at 120°C for 1 hour, and then calcine it at 500°C for 1.5 hours to obtain adsorbent B.
[0059] Four samples were randomly selected from adsorbent B and numbered B1, B2, B3 and B4 respectively. The test results of the component content, static water adsorption capacity and crush resistance of each sample are shown in Table 1 and Table 2.
[0060] Example 3
[0061] This embodiment provides a method for preparing an adsorbent, the specific steps of which are as follows:
[0062] Step 1: Mix 471g of 13X molecular sieve raw powder (with a water content of 15%), 706g of kaolin (with a water content of 15%) and 1324g of water at room temperature for 1 hour to form a uniform slurry. Then, use a peristaltic pump to send the slurry into a spray drying tower and spray granulate it through an atomizing wheel to obtain microspheres.
[0063] The average particle size of the microspheres is 40 μm, and the proportion of microspheres with a particle size distribution of 20-80 μm is 90 wt%.
[0064] The spray drying tower has an internal temperature of 200℃, a peristaltic pump speed of 40 rpm, and an atomizing wheel speed of 13,000 rpm.
[0065] Step 2: Place the above microspheres into a coating machine (model BY300A) for rotational molding at a speed of 70 rpm, while spraying a total of 428 grams of water until the microspheres grow into moist spheres of 1.6-2.5 mm, which is the adsorbent precursor; dry the adsorbent precursor at 120°C for 1 hour, and then calcine it at 500°C for 1.5 hours to obtain adsorbent C.
[0066] Four samples were randomly selected from adsorbent C and numbered C1, C2, C3 and C4 respectively. The test results of the component content, static water adsorption capacity and crush resistance of each sample are shown in Table 1 and Table 2.
[0067] Example 4
[0068] This embodiment provides a method for preparing an adsorbent, the specific steps of which are as follows:
[0069] Step 1: Mix 824g of 13X molecular sieve raw powder (with a water content of 15%), 354g of kaolin (with a water content of 15%) and 1324g of water at room temperature for 1 hour to form a uniform slurry. Then, use a peristaltic pump to send the slurry into a spray drying tower and spray it through an atomizing wheel to obtain microspheres.
[0070] The average particle size of the microspheres is 29 μm, and the proportion of microspheres with a particle size distribution of 20-80 μm is 85 wt%.
[0071] The spray drying tower has an internal temperature of 230°C, a peristaltic pump speed of 40 rpm, and an atomizing wheel speed of 15,000 rpm.
[0072] Step 2: Place the above microspheres into a coating machine (model BY300A) for rotational molding at a speed of 50 rpm, while spraying a total of 523 grams of water until the microspheres grow into moist spheres of 1.6-2.5 mm, which is the adsorbent precursor; dry the adsorbent precursor at 120°C for 1 hour, and then calcine it at 500°C for 2 hours to obtain adsorbent D.
[0073] Four samples were randomly selected from adsorbent D and numbered D1, D2, D3 and D4 respectively. The test results of the component content, static water adsorption capacity and crush resistance of each sample are shown in Table 1 and Table 2.
[0074] Comparative Example 1
[0075] This comparative example provides a method for preparing an adsorbent, the specific steps of which are as follows:
[0076] 1125g of 4A molecular sieve raw powder (with a moisture content of 20%) and 118g of kaolin (with a moisture content of 15%) were mixed in a kneader to form a mixed powder. The mixed powder was then placed in a coating machine (model BY300A) and gradually rotated into spherical particles at a speed of 50 rpm. A total of 600g of water was sprayed while rotating the machine until the particles grew into moist spheres of 1.6-2.5mm. The moist spheres were dried at 120℃ for 1 hour and then calcined at 500℃ for 2 hours to obtain adsorbent E.
[0077] Four samples were randomly selected from adsorbent E and numbered E1, E2, E3 and E4 respectively. The test results of the component content, static water adsorption capacity and crush resistance of each sample are shown in Table 1 and Table 2.
[0078] Comparative Example 2
[0079] This comparative example provides a method for preparing an adsorbent, the specific steps of which are as follows:
[0080] 1059 g of 13X molecular sieve raw powder (with a moisture content of 15%) and 118 g of kaolin (with a moisture content of 15%) were mixed in a kneader to form a mixed powder. The mixed powder was then placed in a coating machine (model BY300A) and gradually rotated into spherical particles at a speed of 50 rpm. A total of 650 g of water was sprayed while rotating the machine until the particles grew into moist spheres of 1.6-2.5 mm. The moist spheres were dried at 120°C for 1 hour and then calcined at 500°C for 2 hours to obtain adsorbent F.
[0081] Four samples were randomly selected from adsorbent F and numbered F1, F2, F3 and F4 respectively. The test results of the component content, static water adsorption capacity and crush resistance of each sample are shown in Table 1 and Table 2.
[0082] Comparative Example 3
[0083] This comparative example provides a method for preparing an adsorbent, the specific steps of which are as follows:
[0084] 875g of 4A molecular sieve raw powder (with a moisture content of 20%) and 353g of kaolin (with a moisture content of 15%) were mixed in a kneader to form a mixed powder. The mixed powder was then placed in a coating machine (model BY300A) and gradually rotated into spherical particles at a speed of 60 rpm. A total of 500g of water was sprayed while rotating the machine until the particles grew into moist spheres of 1.6-2.5mm. The moist spheres were dried at 120℃ for 1 hour and then calcined at 500℃ for 1.5 hours to obtain adsorbent G.
[0085] Four samples were randomly selected from adsorbent G and numbered G1, G2, G3 and G4 respectively. The test results of the component content, static water adsorption capacity and crushing resistance of each sample are shown in Table 1 and Table 2.
[0086] Comparative Example 4
[0087] This comparative example provides a method for preparing adsorbent strip particles, the specific steps of which are as follows:
[0088] Step 1: Mix 875g of 4A molecular sieve raw powder (with a water content of 20%), 353g of kaolin (with a water content of 15%) and 1272g of water at room temperature for 1 hour to form a uniform slurry. Then, use a peristaltic pump to send the slurry into a spray drying tower and spray it through an atomizing wheel to obtain microspheres.
[0089] The average particle size of the microspheres is 70 μm, and the proportion of microspheres with a particle size distribution of 20-80 μm is 91 wt%.
[0090] The spray drying tower has an internal temperature of 150°C, a peristaltic pump speed of 50 rpm, and an atomizing wheel speed of 8000 rpm.
[0091] Step 2: Place the above microsphere particles into a kneader and add 380 grams of water to knead. Then transfer the kneaded material into a screw extruder for extrusion molding to obtain strip-shaped particles with a diameter of 1.5-1.7 mm and a length of 1-6 mm. Dry the strip-shaped particles at 120°C for 1 hour, and then calcine them at 500°C for 1 hour to obtain adsorbent strip-shaped particles H.
[0092] Four samples were randomly selected from the adsorbent strip particles H and numbered H1, H2, H3 and H4 respectively. The test results of the component content, static water adsorption capacity and crush resistance of each sample are shown in Table 1 and Table 2.
[0093] To analyze the stability of the content of various components in the adsorbents prepared in Examples 1-4 and Comparative Examples 1-4, the relative standard deviation of the content of the main components in the adsorbents prepared in each example and comparative example was calculated to more intuitively represent the degree of fluctuation in elemental composition, and the results are recorded in Table 1.
[0094] In Table 1, the formula for calculating the relative standard deviation (RSD) is: RSD = (standard deviation / mean) × 100%; where the standard deviation is the sample standard deviation (S), and the formula for calculating the sample standard deviation is shown in Equation (I):
[0095]
[0096] In equation (Ⅰ), Xi Represents each sample data point, This represents the average value of the sample data points, and n represents the number of samples selected.
[0097] Table 1. Statistical results of the content (wt%) of major components in the adsorbent
[0098]
[0099]
[0100] As can be seen from Table 1, the content of each component in the adsorbents prepared in Examples 1-4 is relatively stable. Furthermore, comparing Examples 2 and Comparative Examples 3-4, it can be seen that when the amounts of molecular sieve powder and kaolin are the same, the relative standard deviations of Na2O, Al2O3, and SiO2 in the adsorbents prepared using the method of this invention are much smaller than those in Comparative Examples 3-4. Therefore, the adsorbent prepared by the method provided by this invention has a more uniform elemental composition, thereby enabling more precise control over the component content in the adsorbent spheres.
[0101] Furthermore, the static water adsorption capacity and crushing resistance of the adsorbents prepared in Examples 1-4 and Comparative Examples 1-4 were tested, and the relative standard deviation of the static water adsorption capacity and crushing resistance of each sample selected in adsorbent AH was calculated using the same method. The results are shown in Table 2.
[0102] Table 2. Statistical results of static water adsorption capacity and crushing resistance in the adsorbent
[0103]
[0104] As can be seen from Table 2, the static water adsorption capacity of the same batch of adsorbents prepared in Examples 1-4 fluctuated little, with a relative standard deviation of 0.77%-2.08%. Among them, comparing Example 2 and Comparative Examples 3-4, it can be seen that when the amounts of molecular sieve powder and kaolin are the same, the adsorption performance of the adsorbent prepared by the method provided by the present invention is more stable.
[0105] Furthermore, the adsorbents prepared in Examples 1-4 exhibit high crushing strength, reaching up to 45.2 N, and the relative standard deviation of crushing strength is 1.2%-1.87%, indicating that the adsorbent microspheres prepared by the method provided in this invention have excellent and stable mechanical strength.
[0106] In summary, this invention prepares adsorbents by sequentially employing mixing and pulping, spray drying microsphere granulation, and direct rotational molding of the granulated microspheres. During spray drying, the silica and alumina in the molecular sieve powder and clay components undergo strong bonding due to high-temperature dehydration, resulting in microspheres with uniform elemental composition and high mechanical strength. Furthermore, by controlling the spray drying process conditions, microspheres with specific particle sizes and fine powder content can be prepared. During rotational molding, the spray-dried microspheres serve as "seeds" for the nucleation stage and provide the homogeneous powder required for microsphere growth. Due to the specific particle size distribution of the granulated microspheres, the compaction between microsphere particles is good, resulting in adsorbents prepared under the same conditions exhibiting uniform elemental composition, stable adsorption performance, and high mechanical strength in the same batch.
Claims
1. A method for preparing an adsorbent, wherein, The preparation method includes: Step 1: Mix the powder and water to form a slurry, then spray the slurry to obtain microspheres. Step 2: The microspheres are rotated and shaped in the presence of a binder to obtain an adsorbent precursor, which is then dried and calcined to obtain the adsorbent. Among the microspheres, the proportion of particles with a diameter distribution of 20-80 μm is ≥85 wt%, and the average particle size of the microspheres is 29-72 μm.
2. The preparation method according to claim 1, wherein, On a dry basis, the mixed powder comprises 40wt%-70wt% molecular sieve raw powder and 30wt%-60wt% clay.
3. The preparation method according to claim 2, wherein, The molecular sieve raw powder is type A molecular sieve raw powder and / or type X molecular sieve raw powder; And / or, the clay is kaolin and / or attapulgite.
4. The preparation method according to claim 1, wherein, The binder comprises one or more of water, starch, and sodium carboxymethyl cellulose.
5. The preparation method according to claim 1, wherein, The spray granulation process is as follows: the mixed slurry is fed into the spray drying tower using a peristaltic pump, and then sprayed and granulated using an atomizing wheel.
6. The preparation method according to claim 5, wherein, The temperature of the spray drying tower is 150-230℃; And / or, the pumping speed of the peristaltic pump is 40-50 rpm; And / or, the rotational speed of the atomizing wheel is 8000-15000 rpm.
7. The preparation method according to claim 1, wherein, The rotational molding is carried out while the adhesive is being sprayed, with a rotation speed of 50-80 rpm.
8. The preparation method according to claim 1 or 7, wherein, During the rotational molding process, the total amount of the sprayed binder accounts for 38wt%-55wt% of the total dry basis of the mixed powder.
9. The preparation method according to claim 1, wherein, The roasting temperature is 450-550℃, and the roasting time is 1-2 hours.
10. An adsorbent prepared by the preparation method according to any one of claims 1-9.
11. The adsorbent according to claim 10, wherein, The adsorbent has a particle size of 1.6-2.5 mm.
12. The adsorbent according to claim 10, wherein, The adsorbent comprises 5wt%-18wt% Na2O, 36wt%-45wt% Al2O3, and 42wt%-50wt% SiO2.
Citation Information
Patent Citations
Zeolite adsorbent and its preparation method
CN101007261A
Adsorbent for removing heavy metals and ammonia nitrogen in waste water as well as preparation method thereof
CN105536696A